Programa Modellus como ferramenta didática no ensino do lançamento oblíquo com atrito dinâmico - DIAS, Carlos Augusto Fonseca (2023)
Currently, we are faced with the increasingly rapid evolution of technology, and the introduction of technologies in the educational field is a reality and the school must follow this development. Thus, the importance of using technology is highlighted, especially with the use of applications and software, as a useful and necessary work tool for meaningful learning and to improve the relationship between students and teachers. Thus, this work has the objective of using educational technologies to explain physical concepts of oblique launch with dynamic friction force, and thus, contribute to improving the teaching and learning process, in addition to showing students and teachers the feasibility of using simulation and computational modeling in Physics teaching. In the field of fulfilling them, the question arises: are the results obtained superior to the traditional teaching method? To verify this viability, an educational product was elaborated. This product is a practical guide on how to use Modellus software for simulation and also computational modeling. An evaluative questionnaire was applied in both groups, test (where the educational product was developed) and control (where there was no development of the educational product), the satisfaction questionnaire was applied only in the test group, in order to answer the question: Is student satisfaction with the use of simulations greater than with the traditional teaching method? After applying the product, most students in the test group demonstrated a better understanding of the basic concepts for this type of movement. In the end, it was possible to observe that the use of computers, as well as the use of Modellus software to simulate and model physical events, in addition to facilitating the teaching and learning process, also make classes more fun and dynamic. In this way, the student becomes the builder of his knowledge, making learning more meaningful.